Análisis de la responsabilidad del Estado por la actividad médico sanitaria estructurada bajo el título de imputación de riesgo. - Gutiérrez Gómez, Julián Camilo (Universidad Antonio Nariño, 2021)
In Colombia for many years the topic of the protection of Human Rights has been coupled with events of massacres and disappearances by State agents in competition with groups outside the law and others belonging to rebel groups, all of these mainly actors in the conflict. armed in Colombia.